2015
DOI: 10.1002/cncr.29326
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive predictors of understanding treatment decisions in patients with newly diagnosed brain metastasis

Abstract: Background Medical decision-making capacity is a higher-order functional skill that refers to a patient’s ability to make informed, sound decisions related to care and treatment. In a medical context, understanding is the most cognitively demanding consent standard and refers to a patient’s ability to comprehend information to the extent that informed decisions can be made. Methods The association between reasoning and cognition was examined using data from 41 patients with diagnosed brain metastasis. All di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(68 citation statements)
references
References 16 publications
3
65
0
Order By: Relevance
“…Hence, cognition is per this description linked to both language and decision-making, which is in coherence with previous findings (e.g. Okonkwo et al, 2007;Gerstenecker et al, 2015). Nevertheless, the general study of linguistics covers a number of elements, discussed by for example Johansson and Manninen (2012).…”
Section: IVsupporting
confidence: 87%
See 2 more Smart Citations
“…Hence, cognition is per this description linked to both language and decision-making, which is in coherence with previous findings (e.g. Okonkwo et al, 2007;Gerstenecker et al, 2015). Nevertheless, the general study of linguistics covers a number of elements, discussed by for example Johansson and Manninen (2012).…”
Section: IVsupporting
confidence: 87%
“…Several previous studies (e.g. Gerstenecker et al, 2015;Grisso & Appelbaum, 1998;Dunn & Jeste, 2001) have showed that verbal function is associated to the decision-making capacity. Palmer and Savla (2007) underscored certain central abilities associated with the cognitive process of consent capacity, such as short-term memory (e.g.…”
Section: Associated Cognitive and Linguistic Functionsmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, it has been found that patient understanding varied directly with the vocabulary subtest of the Wechsler Adult Intelligence Scale, 19 , 20 and Gerstenecker and colleagues found that verbal memory and fl uency were highly associated with understanding as defi ned by the Capacity to Consent to Treatment Instrument. 21 These studies, although promising, still deploy neuropsychological tests that are reliant on expressive language. To apply these fi ndings to patients with communication impairments would require further research on neuropsychological tests that do not involve expressive language.…”
Section: Step 3: Can Compensatory Measures Of Decision-making Capacitmentioning
confidence: 99%
“…To accomplish this goal, we administered a comprehensive neuropsychological test battery and performance‐based measure of research consent capacity to all study participants. Based on our previous works, 1,8‐10 we hypothesize that impairments in the ability to provide informed consent would be largely driven by impairments on cognitive measures of verbal fluency and short‐term verbal memory. We further hypothesize that history of chemotherapy, steroid treatment, and anticonvulsant use would also be associated with the ability to provide informed consent.…”
Section: Introductionmentioning
confidence: 99%